Novel Bismuth-Oxyhalide-Based Materials and their Applications - Gondal, Mohammed A.; Xiaofeng, Chang; Dastageer, Mohamed A.; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2017)
This book provides a comprehensive overview of a series of bismuth oxyhalide compounds of BiOX (X=F, Cl, Br, I), in terms of their microstructure, electronic/band structure, preparation techniques, optical properties and their applications. The book brings together, for the first time, a compilation of advances in this area, including results achieved at the authors' lab (such as ultra-microscopy characterization by means of aberration-corrected STEM), offering a valuable guide for researchers and students alike.
Introduction to Bismuth Oxyhalides -- Microstructure, Morphology and Surface Structure of Bismuth Oxyhalides -- Band Structure Band Energy and Density of States -- Optical Properties of Bismuth Oxyhalides -- Preparation Techniques and Crystal Growth Processes -- Modified Bismuth Oxyhalide Semiconductors -- Applications of Bismuth Oxyhalides -- Future Prospects of Bismith Oxyhalides.
Keywords: Optical materials; Materials; Chemistry, Technical; Optical Materials; Materials Engineering; Industrial Chemistry